The Baby in the Hat - Ahlberg, Allan; Illustrated by André Amstutz (London Walkar Books, 2008)
Catching a baby in his hat sets off a series of adventures for a young nineteenth-century English boy as he becomes a sea captain and finds a surprising mate.
Include Color Illustrations
Keywords: Seafaring life